MENCIPTAKAN BATIK MANGGARANG SEBAGAI IKON DALAM MEMBANGKITKAN KEMBALI WISATA MANGROVE - Ade Sintia; Asih Wayuningsih; Shania Khairunisa; Hani Permatasari (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
The existence of mangroves directly plays a role in maintaining the balance of the coastal ecosystem and providing benefits, economy and social base of the local community. One of them is that mangroves are used as tourist attractions. However, it is very unfortunate that during pandemic, mangrove tourism has become empty pf visitors. Many new innovations have emerged to revive mangrove tourisme, one of which is the author who created batik. Cirebon is famous for its batik, namely Mega Mendung,, so Manggarang batik will become its characteristic and Mundu. Batik is also one of Indonesia’s indigenous heritage which has been recognized worldwide. Manggarang batik is designed with special motifs of Mangroves, Resources such as shells and also a tool for finding shells, namely the rake (garok).the process of making batik takes quite a long time, approximately 1 to 3 months, so in this article the batik is still in the decolorization.